1991
DOI: 10.1103/physrevlett.67.2351
|View full text |Cite
|
Sign up to set email alerts
|

Broken symmetry and the formation of hot-electron domains in real-space-transfer transistors

Abstract: Real-space-transfer (RST) transistors are studied theoretically. In a symmetric configuration, with no voltage applied between the channel electrodes, we find anomalous steady states in which the RST is driven by the fringing field from the collector electrode. Some of these states are unconditionally stable and hence accessible experimentally. Our study elucidates the formation of hot-electron domains, which is shown to be a discontinuous process that passes the control of electron heating from the drain to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 17 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Presently, we consider the plausibility of the hot-spot model in conventional, nongated, real space transistors [9], [lo]. As noted earlier, the source current behaves as a conventional FET over all gate bias values while the gate current, remains negligibly small.…”
Section: Irr Measured Device Performancementioning
confidence: 99%
“…Presently, we consider the plausibility of the hot-spot model in conventional, nongated, real space transistors [9], [lo]. As noted earlier, the source current behaves as a conventional FET over all gate bias values while the gate current, remains negligibly small.…”
Section: Irr Measured Device Performancementioning
confidence: 99%
“…In some sense, one can draw an analogy between the light-current characteristics of a laser and the current-voltage characteristics of various negative differential resistance devices, such as those based on tunneling or real-space transfer nonlinearities. For example, the numerical study of real-space transfer transistors [22] revealed the existence of multiply connected current-voltage characteristics, with several stable points at a given voltage. In some cases, the anomalous branch may even be unconditionally stable, but even if it is not, its very presence should have a pronounced effect on the large-signal dynamics of laser operation.…”
Section: Two-valued Characteristics: Gain-current and Light-currentmentioning
confidence: 99%
“…The equation for the critical tolerable parameters [equality in (16)] can be rewritten as follows: (22) where is the maximum tolerable mirror loss. Equation 22has an evident meaning.…”
Section: B Critical Tolerable Values Of Andmentioning
confidence: 99%
“…The demonstrated combined optoelectronic method is different from and complementary to the all-optical techniques that have been used to measure the energy relaxation of hot carrier plasma, 9,10 the relaxation of hot minority carriers due to cold majority carriers, 11 and the relaxation of hot carrier plasma in the presence of a cold plasma background. 12 Second, although the operation and carrier transport in CHINTs has been investigated both theoretically and experimentally with conventional dc and microwave techniques, [13][14][15][16]3 optoelectronic techniques provide an alternate picture and an understanding of the device's optical characteristics. Such advantages have already been demonstrated with bipolar transistors.…”
Section: Introductionmentioning
confidence: 99%